2022
DOI: 10.1186/s12888-022-03915-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cognitive behavioral therapy program on mental health status among medical student in Palestine during COVID pandemic

Abstract: Background The COVID-19 pandemic had a profound psychological influence on everyone in society, and the impact it had on students, particularly medical students, cannot be underestimated. The main purpose of this study is to (1) determine the prevalence of mental disorders among medical students and their associated factors, and (2) examine the effectiveness of cognitive behavior therapy on mental health problems among medical students. Methods Bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 58 publications
1
8
2
1
Order By: Relevance
“…Previous studies indicated that drug addiction in adults is categorized by problems in emotional regulation which explore the significance of new and specific treatment methods [22]. Finally research witnessed that exposure to CBT programs can reduce psychological problems [23].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicated that drug addiction in adults is categorized by problems in emotional regulation which explore the significance of new and specific treatment methods [22]. Finally research witnessed that exposure to CBT programs can reduce psychological problems [23].…”
Section: Resultsmentioning
confidence: 99%
“…The control group was just provided with general information about mental health via WhatsApp messages. The CBT intervention program showed a significant improvement in depression, anxiety, and social dysfunction for the study group compared to the control [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…All the included studies followed a pretest-posttest design. Moreover, four were supplemented by an additional follow-up examination [ 27 , 29 , 30 , 35 ]. An analysis of the statistical methods used revealed that three authors used univariate pre-post methods (Wilcoxon test, t-test, Mann-Whitney U test) [ 34 , 35 , 38 ], six authors used linear models [ 27 , 29 , 32 , 33 , 36 , 37 ], three studies employed analysis of variance [ 28 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive‐behavioural therapy (CBT), in particular, is a psychoanalytic treatment modality conducted under professional guidance that seeks to help individuals modify dysfunctional thinking and behaviour as a way to help solve problems that favour the experience of anxious symptoms 72 . CBT‐based programmes lasting 8 weeks and carried out remotely have achieved positive effects in reducing anxiety in medical students during the pandemic 73 . Mindfulness‐based stress reduction (MBSR) is also a well‐established programme that has proven to reduce anxiety in individuals.…”
Section: Discussionmentioning
confidence: 99%